Small Modular Reactors (SMRs) - A Future Nuclear Power Option - Dr. Syed Javaid Khurshid (CISS Insight Journal, 2018)
Pakistan is facing energy deficiency for the last three decades, to overcome this deficiency Pakistan plans to expand its nuclear energy sector on large scale. The Small Modular Reactors (SMRs) is a futuristic technology and considered to be the game changer in decade to come. It will help to overcome the deficiencies of nuclear power production while bringing the initial capital cost down. The SMRs technology can help to overcome many problems such as the financial requirement by lowering initial cost investment, beside this usage of very less space, easily transportable, easy increment in power capacity, with more safety and security and ease of dismantling with less cost after completion of life span. The article discusses the energy scenario of Pakistan, mentioning nuclear energy as a solution, the benefits of SMRs technology, development and deployment stages of various type of SMRs under construction worldwide, their advantages and benefits.